2003
DOI: 10.1029/2002gc000387
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of biological activity in Hawaiian subsurface basalts

Abstract: [1] The Hawaii Scientific Drilling Program (HSDP) cored and recovered igneous rock from the surface to a depth of 3109 m near Hilo, Hawaii. Much of the deeper parts of the hole is composed of hyaloclastite (fractured basalt glass that has been cemented in situ with secondary minerals). Some hyaloclastite units have been altered in a manner attributed to microorganisms in volcanic rocks. Samples from one such unit (1336 m to 1404 m below sea level) were examined to test the hypothesis that the alteration was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
106
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(110 citation statements)
references
References 69 publications
(109 reference statements)
3
106
0
1
Order By: Relevance
“…This is the first report of this clade in this environment, as previous studies that examined the archaeal communities in basalts revealed only Marine Group I Crenarchaeota Fisk et al, 2003;Lysnes et al, 2004;Mason et al, 2007). Recently, quantitative analyses of the microbial communities in basalts revealed that Archaea comprise 4-12% and 0.02% or less of the prokaryotic communities (Santelli et al, 2008;Einen et al, 2008), respectively.…”
Section: Phylogenetic Analysismentioning
confidence: 64%
See 3 more Smart Citations
“…This is the first report of this clade in this environment, as previous studies that examined the archaeal communities in basalts revealed only Marine Group I Crenarchaeota Fisk et al, 2003;Lysnes et al, 2004;Mason et al, 2007). Recently, quantitative analyses of the microbial communities in basalts revealed that Archaea comprise 4-12% and 0.02% or less of the prokaryotic communities (Santelli et al, 2008;Einen et al, 2008), respectively.…”
Section: Phylogenetic Analysismentioning
confidence: 64%
“…Although these estimates are disparate, they do reveal that Archaea are a minor component in the overall microbial communities that reside in basalt. Although Archaea are less prevalent, they are ubiquitous in basalts and have been reported in all studies that assayed for their presence Fisk et al, 2003;Lysnes et al, 2004;Mason et al, 2007;Einen et al, 2008;Santelli et al, 2008). Further, as discussed previously, a clade of Marine Group I Archaea appears to be endemic to basalt (Mason et al, 2007).…”
Section: Phylogenetic Analysismentioning
confidence: 87%
See 2 more Smart Citations
“…The alteration process may be significant in understanding the reactions and compositional exchange between seawater and basalt glass at low temperatures, thereby providing an analogue system for the early history of fluids that circulate through mid-ocean hydrothermal systems. Signs of microbial involvement in the alteration process are evident as filamentous channels in glass, but only within a restricted portion of the core between about 1080 mbsl and 1460 mbsl (Walton and Schiffman, 2003;Walton, 2008;Fisk et al, 2003). This re-striction suggests that microbes infected the hyaloclastites early in their history but are not very active at present.…”
Section: Geochemical Structure Of the Hawaiian Mantle Plumementioning
confidence: 89%